Venlafaxine-Induced Orthostatic Hypotension in a Geriatric Patient - Chikkaramanjegowda, Vidyashree; de Leon, Jose (Case Reports in Psychiatry, 2013)
Venlafaxine is not usually associated with risk of orthostatic hypotension. A 65-year-old US Caucasian female taking 225 mg/day of venlafaxine extended-release developed symptomatic orthostatic hypotension. The systolic and diastolic blood pressure dropped by 25 and 18 mm Hg, respectively, from supine position to standing position within 3 minutes. The patient was otherwise healthy and the orthostatic hypotension resolved with venlafaxine discontinuation. This was a probable venlafaxine adverse drug reaction according to the Naranjo scale. This case contributes to the scarce literature that indicates that clinicians need to be aware that occasionally venlafaxine can induce clinically significant orthostatic hypotension, particularly in geriatric patients. Our patient did not have orthostatic hypotension when she was taking venlafaxine at 60 years of age in higher venlafaxine doses (300 mg/day) but developed this adverse drug reaction when venlafaxine was restarted at the geriatric age. This case indicates that a history of prior tolerance to venlafaxine does not guarantee tolerance after 65 years of age. If a clinician decides to use venlafaxine in geriatric patients, the clinician should warn the patient about the risk of orthostatic hypotension and consider very slow titration and low doses.